A forensic analysis of the Global South: between performative expression, analytic concept and reality under construction - Rafael Grasa (Revista CIDOB d'Afers Internacionals)
This paper asks whether it is appropriate to use the term “Global South” from an analytical and explanatory viewpoint, despite it being an essentially contentious concept that combines performative and analytic use and refers to a reality that is under construction. To do so it conducts a forensic analysis, focusing on facts and evidence. The answer is yes. To arrive at that conclusion, it reconstructs two of its driving forces: the political assertion of the Third World programme in aspirational rather than territorial terms; and the impact of the reimagination of International Relations as an inclusive discipline and of the demand for a new, more consensual international order than those that emerged in the aftermath of the two world wars and the Cold War. The paper defines Global South as a shifting conglomeration of state and transnational actors and proposes criteria to determine its universe via various concentric circles.